Research of flavor profiles of the red and white wines of Shabo terroir - Иукуридзе, Элдар Жораевич; Ткаченко, Оксана Борисовна; Гураль, Лариса Сергеевна; Лозовская, Татьяна Сергеевна (Technology audit and production reserves, 2016)
The article presents the results of comprehensive research in the SARCO laboratory (France), which allowed establishing the list and the concentration of flavor compounds responsible for the high-quality, secondary and tertiary flavor of wines. Ratings of the typical flavor of wine is a complex task because the high-quality features depend not on the specific chemical component, but from the general flavor-active compounds present in grapes and wine. Studies to determine the typical flavor of grape varieties of Shabo terroir previously carried out and there are no objective data in addition to sensory evaluation. In the world scientific research practice, methodical approaches were developed to sensory evaluation of flavor / bouquet and wine tasting, which allow numerically reflect its individual characteristics on the intensity of shades. However, the subjectivity of sensory method does not allow using it as the main one. A combination of sensory and analytical techniques is particularly important in addressing the influence of interactions with non-volatile flavor compounds and other volatile compounds. The aim of the studies was characteristic flavor profile of red (Merlot and Cabernet Sauvignon) and white wines (Chardonnay and Telti-Kuruk) produced in LLC «Industrial-trading company Shabo». Studies to determine the flavor profile of Shabo terroir wines were held for the first time. The studies found that red and white wines are present in sufficiently high concentrations of lactones: in Cabernet Sauvignon 1,6-2,0 times greater than in Merlot, in Telti-Kuruk 2,0-2,4 times greater than in Chardonnay. It was found that the varietal flavor of wines Merlot and Cabernet Sauvignon is a 3-isobutyl-2-methoxypyrazine. The primary flavors as actively influence the bouquet of white wines Chardonnay and Telti-Kuruk are β -damascenone, β-ionone and 3-mercapto-1-hexanol. 4-mercapto-4-methyl-2-pentanone, which is the «calling card» of wine Sauvignon Blanc, was found in small quantities only in the white wine Telti-Kuruk.